EXPLORING COMPENSATION SATISFACTION TO ENHANCE MOTIVATION AND REDUCE TURNOVER INTENTION AMONG EMPLOYEE OF PRIVATE BOTTLED WATER COMPANY IN INDONESIA - Arif Partono Prasetio; Elvira Azis; Grisna Anggadwita (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2019)
The bottled water industry faces rapid development. This expansion increases the business competition between companies. One of important aspect to win the competition is to have the right resources. Human resources have long been known as important factor in organization. They need to have and enhance their human capital if they want to have competitive advantage which is hard to compete. Therefore, every business organization should maintain their outstanding employees. This study aims to identify the efforts of private organizations in retaining employees by analysing the role of compensation satisfaction and motivation. This study uses quantitative method with bootstrapping approach. The questionnaire was distributed to 200 employees and gets 133 usable responses with response rate of 66.5%. Using mediation analysis the study found motivation did not mediate the relation between compensation satisfaction and turnover intention. Compensation had direct effect on turnover intention which means the organization must put their thoughts on how to manage compensation program. Though better compensation could lead to higher work motivation, it turn out that motivated employee tends to search the opportunity outside the organization. Other important thing is that the human resources should start identifying why motivated employees want to leave the organization.